Comparative Test of Ret-He Examination in Diagnosis of Iron Deficiency in Pregnant Women - Nugraha, Gilang; Masruroh, Nur; Kurniasari, Diyan Wahyu (Medical Laboratory Technology Journal, 2020)
The most common cause of anemia is iron deficiency, which found in 50% of anemia cases. There are 66.7% of pregnant women in Indonesia that still lack iron intake. Reticulocyte hemoglobin equivalent (Ret-He) examination as a single parameter is the initial indicator of iron deficiency, considered more sensitive in detecting iron reserves in the body. This study aims to determine the effectivity of the Ret-He examination as a single parameter in establishing the diagnosis of iron deficiency in pregnant women. This research was conducted on 30 pregnant women. The sensitivity, specificity, and predictive value of Ret-He were determined by comparing the results of the biochemical examination of iron profiles. Iron deficiency defined as an abnormal examination result on two or more biochemical parameters, which were SI <50 µg/dL, TIBC >425 µg/dL, serum ferritin <10 ng/mL and Transferrin Saturation <15.0%. Between 30 pregnant women, there were 18 (60%) with iron deficiency and 12 (40%) without iron deficiency. Ret-He levels were significantly lower in pregnant women with iron deficiency (P=0.008). A decrease in the Ret-He level in iron deficiency positively correlated with serum Ferritin (r=0.433). The effectivity of the Ret-He examination had an AUC value of 0.785 (P=0.009). Ret-He diagnostic reliability had at a cut-off value of 27.2 pg with sensitivity (87.5%), specificity (50.0%), positive predictive value (38.9%), and negative predictive value (91.7%). Ret-He examination is a useful marker of iron deficiency in pregnant women so that it can be applied for screening or as a routine examination.